Nonaqueous electrolyte storage element and storage device

A non-aqueous electrolytic storage element with lithium transition metal composite oxides and fluorine solvent stabilizes lithium metal, addressing electrolyte decomposition and enhancing discharge capacity and cycle performance.

JP7622651B2Active Publication Date: 2025-01-28GS YUASA CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021569754
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-01-06
Filing Date
2020-11-26
Publication Date
2025-01-28
Estimated Expiration
2040-11-26

AI Technical Summary

Technical Problem

Non-aqueous electrolytic secondary batteries using lithium metals in the negative electrode suffer from significant decomposition of the electrolyte due to the high reactivity of lithium metal, leading to decreased rechargeable and discharge cycle performance.

Method used

A non-aqueous electrolytic storage element with a negative electrode containing lithium metal and a positive electrode using specific lithium transition metal composite oxides, such as α-NaFeO2, is formulated with controlled molar ratios of lithium to transition metals, combined with a fluorine solvent to form a protective film on the lithium metal surface, enhancing cycle performance.

Benefits of technology

The solution provides a non-aqueous electrolytic storage element with improved discharge capacity and charging and discharge cycle performance by suppressing the decomposition of the electrolyte and maintaining lithium availability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007622651000002
    Figure 0007622651000002
  • Figure 0007622651000003
    Figure 0007622651000003
  • Figure 0007622651000001
    Figure 0007622651000001
Patent Text Reader

Abstract

The present invention belongs to the technical field of non-aqueous electrolyte power storage elements, addresses the technical problem of providing a non-aqueous electrolyte power storage element having excellent discharge capacity and charge-discharge cycle performance, and solves this technical problem by providing a non-aqueous electrolyte power storage element in which a non-aqueous electrolyte solution contains a fluorinated solvent, a negative electrode active material contains lithium metal, and a positive electrode active material contains a lithium-transition metal composite oxide having an α-NaFeO2 structure, wherein: the lithium-transition metal composite oxide is a first composite oxide which contains lithium and a transition metal element including Mn and in which the molar ratio of lithium relative to the total transition metal element content is greater than 1 and the molar ratio of Mn relative to the total transition metal element content is greater than 0.5, or a second composite oxide which contains lithium and transition metal elements including Ni, Co and Mn and in which the molar ratio of lithium relative to the total transition metal element content is 1 or more; and the molar ratio of Mn relative to the total transition metal element content is 0.5 or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a nonaqueous electrolyte electricity storage element and an electricity storage device. [Background technology]

[0002] Non-aqueous electrolyte secondary batteries, such as lithium ion secondary batteries, are widely used in electronic devices such as personal computers and communication terminals, automobiles, etc., due to their high energy density. The non-aqueous electrolyte secondary batteries generally have a pair of electrodes electrically isolated by a separator and a non-aqueous electrolyte interposed between the electrodes, and are configured to charge and discharge by transferring ions between the electrodes. In addition, capacitors such as lithium ion capacitors and electric double layer capacitors are also widely used as storage elements other than non-aqueous electrolyte secondary batteries.

[0003] In recent years, in order to increase the energy density of the secondary battery, there has been a demand for a secondary battery with a higher voltage and a higher capacity of the negative electrode. By increasing the voltage of the secondary battery, the energy density can be improved, but when a typical layered lithium transition metal composite oxide is used as a positive electrode active material, sufficient capacity cannot be obtained on the high voltage side. On the other hand, lithium metal has a significantly larger discharge capacity per active material mass than graphite, which is currently widely used as a negative electrode active material for lithium ion secondary batteries. For this reason, a nonaqueous electrolyte secondary battery using metallic lithium as a negative electrode active material has been proposed (see JP 2011-124154 A). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2011-124154 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, in non-aqueous electrolyte secondary batteries using lithium metal in the negative electrode, the decomposition of the non-aqueous electrolyte is significantly accelerated due to dissolution and precipitation of the negative electrode containing lithium metal during charging and discharging due to the high activity of lithium metal, which may result in a decrease in charge-discharge cycle performance.

[0006] The present invention has been made in view of the above circumstances, and has an object to provide a nonaqueous electrolyte electricity storage element and electricity storage device that are excellent in discharge capacity and charge / discharge cycle performance. [Means for solving the problem]

[0007] One aspect of the present invention made to solve the above problems is a non-aqueous electrolyte storage element comprising: a negative electrode having a negative electrode active material layer containing a negative electrode active material; a positive electrode having a positive electrode active material layer containing a positive electrode active material; and a non-aqueous electrolyte, wherein the non-aqueous electrolyte contains a fluorinated solvent, the negative electrode active material contains lithium metal, and the positive electrode active material contains a lithium transition metal composite oxide having an α-NaFeO2 structure, the lithium transition metal composite oxide is a first composite oxide or a second composite oxide, the first composite oxide contains a transition metal element containing manganese and lithium, a molar ratio of the lithium to a total content of the transition metal elements in the first composite oxide is greater than 1 and a molar ratio of the manganese to a total content of the transition metal elements is greater than 0.5, and the second composite oxide contains a transition metal element containing nickel, cobalt, and manganese and lithium, a molar ratio of the lithium to a total content of the transition metal elements in the second composite oxide is 1 or more, and a molar ratio of the manganese to a total content of the transition metal elements is 0.5 or less.

[0008] Another aspect of the present invention is an electricity storage device including two or more nonaqueous electrolyte storage elements, and including one or more of the nonaqueous electrolyte storage elements according to the other aspect of the present invention. Effect of the Invention

[0009] According to the present invention, it is possible to provide a nonaqueous electrolyte storage element having excellent discharge capacity and charge / discharge cycle performance. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a perspective view showing a nonaqueous electrolyte storage element according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing an electricity storage device formed by assembling a plurality of nonaqueous electrolyte electricity storage elements according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] A nonaqueous electrolyte storage element according to one embodiment of the present invention includes a negative electrode having a negative electrode active material layer containing a negative electrode active material, a positive electrode having a positive electrode active material layer containing a positive electrode active material, and a nonaqueous electrolyte, wherein the nonaqueous electrolyte contains a fluorinated solvent, the negative electrode active material contains lithium metal, and the positive electrode active material contains a lithium transition metal composite oxide having an α-NaFeO2 structure, the lithium transition metal composite oxide is a first composite oxide or a second composite oxide, the first composite oxide contains a transition metal element containing manganese and lithium, a molar ratio of the lithium to a total content of the transition metal elements in the first composite oxide is greater than 1 and a molar ratio of the manganese to a total content of the transition metal elements is greater than 0.5, and the second composite oxide contains a transition metal element containing nickel, cobalt, and manganese and lithium, a molar ratio of the lithium to a total content of the transition metal elements in the second composite oxide is 1 or more, and a molar ratio of the manganese to a total content of the transition metal elements is 0.5 or less.

[0012] The nonaqueous electrolyte storage element has excellent discharge capacity and charge / discharge cycle performance because the nonaqueous electrolyte contains a fluorinated solvent, the negative electrode active material contains lithium metal, and the positive electrode active material contains a specific lithium transition metal composite oxide having an α-NaFeO2 structure. The reason for this is unclear, but is presumed to be as follows. As described above, in a nonaqueous electrolyte secondary battery using lithium metal in the negative electrode, the decomposition of the nonaqueous electrolyte is significantly promoted due to the high activity of lithium metal, which is accompanied by dissolution and deposition of the negative electrode containing lithium metal during charging and discharging. Therefore, the charge / discharge cycle performance may be deteriorated. On the other hand, since a fluorinated solvent forms a good coating on the lithium metal surface of the negative electrode, if the nonaqueous electrolyte contains a fluorinated solvent, continuous reduction and decomposition of the nonaqueous electrolyte on the lithium metal is suppressed, and the charge / discharge cycle performance is improved. It is believed that the nonaqueous electrolyte storage element has excellent discharge capacity and charge / discharge cycle performance by combining a negative electrode using lithium metal, a nonaqueous electrolyte containing a fluorinated solvent, and a positive electrode active material containing a specific lithium transition metal composite oxide.

[0013] It is preferable that the lithium transition metal composite oxide contains the first composite oxide. When the first composite oxide is used as the positive electrode active material, the chemical conversion proceeds further with the charge / discharge cycle, so that high cycle performance can be obtained. That is, in the lithium transition metal composite oxide according to the first composite oxide, it is considered that the lithium element is present not only at the lithium site in the crystal structure but also at the transition metal site before charge / discharge. However, in the charging process of the non-aqueous electrolyte storage element using the lithium transition metal composite oxide as the positive electrode active material, the reaction resistance related to the reaction in which the lithium present at the transition metal site is extracted is considered to be larger than the reaction resistance related to the reaction in which the lithium present at the lithium site is extracted. From this, it is considered that when the charge / discharge cycle of the non-aqueous electrolyte storage element is repeated, the lithium present at the transition metal site is not completely extracted at the first charge, but is gradually extracted over the second and subsequent charge cycles. For this reason, when the lithium transition metal composite oxide contains the first composite oxide, even if lithium is consumed in the system of the nonaqueous electrolyte storage element, the lithium present at the transition metal site of the first composite oxide serves as a source to replenish the lithium that is insufficient in the system, and thus, when the lithium transition metal composite oxide is the first composite oxide, the discharge capacity and the charge / discharge cycle performance can be improved.

[0014] The first composite oxide has a peak differential pore volume of 0.2 mm or less in a pore diameter range of 20 nm to 80 nm where the differential pore volume is maximum as determined by the BJH method from an adsorption isotherm using a nitrogen gas adsorption method. 3 / (g·nm) or more is preferably used. In the nonaqueous electrolyte storage element, the nonaqueous electrolyte contains a fluorinated solvent, but since this fluorinated solvent has a relatively high viscosity, it generally tends to have a high reaction resistance with the electrodes, which is not necessarily an advantageous feature in terms of the performance of the storage element. In addition, unlike the second composite oxide, the first composite oxide is accompanied by an oxidation-reduction reaction of oxygen constituting the first composite oxide during charging and discharging, and therefore tends to have a high reaction resistance compared to the second composite oxide. Therefore, when combining the fluorinated solvent and the first composite oxide, it is required to increase the contact interface between the first composite oxide and the nonaqueous electrolyte, i.e., the reaction sites. The nonaqueous electrolyte storage element has a peak differential pore volume of 0.2 mm 3 / (g·nm) or more, the contact interface between the first composite oxide and the nonaqueous electrolyte can be increased, resulting in further improvements in discharge capacity and charge / discharge cycle performance. Here, the "BJH (Barrett-Joyner-Halenda) method" refers to a technique in which the pore shape is assumed to be cylindrical and the pore diameter is calculated from the adsorption isotherm, which is the relationship between the relative pressure when gas molecules are adsorbed onto a sample and the amount of gas molecules adsorbed.

[0015] Hereinafter, a nonaqueous electrolyte storage element according to an embodiment of the present invention will be described in detail. Note that the names of the components (elementary components) used in each embodiment may differ from the names of the components (elementary components) used in the background art.

[0016] <Non-aqueous electrolyte storage element> A nonaqueous electrolyte storage element according to one embodiment of the present invention includes a negative electrode, a positive electrode, and a nonaqueous electrolyte. Hereinafter, a nonaqueous electrolyte secondary battery will be described as an example of a nonaqueous electrolyte storage element. The positive electrode and the negative electrode are usually stacked or wound alternately with a separator interposed therebetween to form an electrode body. This electrode body is housed in a case, and the case is filled with a nonaqueous electrolyte. In the nonaqueous electrolyte secondary battery, the above-mentioned nonaqueous electrolyte is used as the nonaqueous electrolyte. The nonaqueous electrolyte is interposed between the positive electrode and the negative electrode. In addition, as the case, a known metal case, a resin case, or the like that is usually used as a case for a nonaqueous electrolyte secondary battery can be used.

[0017] [Negative electrode] The negative electrode has a negative electrode substrate and a negative electrode active material layer laminated directly or indirectly on at least one surface of the negative electrode substrate. The negative electrode may also have an intermediate layer disposed between the negative electrode substrate and the negative electrode active material layer.

[0018] (Negative electrode substrate) The negative electrode substrate has electrical conductivity. Metals such as copper, nickel, stainless steel, and nickel-plated steel, or alloys thereof, are used as the material of the negative electrode substrate. Among these, copper or copper alloys are preferred. Examples of the form of the negative electrode substrate include foil and vapor deposition film, and foil is preferred from the viewpoint of cost. Therefore, copper foil or copper alloy foil is preferred as the negative electrode substrate. Examples of copper foil include rolled copper foil and electrolytic copper foil. The term "electrically conductive" refers to a material having a volume resistivity of 1×10 measured in accordance with JIS-H0505 (1975). 7 "Non-conductive" means that the volume resistivity is 1×10 7 This means that the resistance is greater than Ω·cm.

[0019] The average thickness of the negative electrode substrate is preferably 2 μm to 35 μm, more preferably 3 μm to 30 μm, even more preferably 4 μm to 25 μm, and particularly preferably 5 μm to 20 μm. By setting the average thickness of the negative electrode substrate within the above range, the strength of the negative electrode substrate can be increased while increasing the energy density per volume of the nonaqueous electrolyte secondary battery. The "average thickness of the substrate" refers to the value obtained by dividing the punched mass when a substrate of a predetermined area is punched out by the true density and punched area of ​​the substrate.

[0020] (Negative electrode active material layer) The negative electrode active material layer contains a negative electrode active material. The negative electrode active material layer contains lithium metal as a negative electrode active material. When the negative electrode active material contains lithium metal, the discharge capacity per active material mass can be improved. The lithium metal includes lithium simple substance as well as lithium alloys. Examples of the lithium alloy include lithium aluminum alloys. The negative electrode containing lithium metal can be manufactured by cutting lithium metal into a predetermined shape or forming it into a predetermined shape.

[0021] Furthermore, the negative electrode active material layer may contain elements such as Na, K, Ca, Fe, Mg, Si, and N.

[0022] The lower limit of the lithium metal content in the negative electrode active material is preferably 80 mass %, more preferably 90 mass %, and even more preferably 95 mass %, while the upper limit of this content may be 100 mass %.

[0023] [Positive electrode] The positive electrode has a positive electrode substrate and a positive electrode active material layer. The positive electrode active material layer contains a positive electrode active material. The positive electrode active material layer is laminated directly or via an intermediate layer along at least one surface of the positive electrode substrate.

[0024] (Positive electrode substrate) The positive electrode substrate has electrical conductivity. As the material of the substrate, metals such as aluminum, titanium, tantalum, stainless steel, etc., or alloys thereof are used. Among these, aluminum and aluminum alloys are preferred in terms of the balance between potential resistance, high electrical conductivity, and cost. In addition, the form of the positive electrode substrate may be foil, vapor deposition film, etc., and foil is preferred in terms of cost. That is, aluminum foil is preferred as the positive electrode substrate. In addition, examples of aluminum or aluminum alloys include A1085, A3003, etc., as specified in JIS-H4000 (2014).

[0025] (Cathode active material layer) The positive electrode active material layer contains a positive electrode active material and, if necessary, any optional components such as a conductive agent, a binder, a thickener, and a filler.

[0026] As the positive electrode active material for a lithium ion secondary battery, a material capable of absorbing and releasing lithium ions is usually used. The positive electrode active material includes a lithium transition metal composite oxide having an α-NaFeO2 type crystal structure. The lithium transition metal composite oxide is a first composite oxide or a second composite oxide. The first composite oxide or the second composite oxide may have a surface coated with another material. The first composite oxide and the second composite oxide may each be a single compound or a mixture of multiple compounds.

[0027] <First composite oxide> The first composite oxide contains a transition metal element including manganese and lithium. In this case, the lithium transition metal composite oxide is a so-called "lithium-excess type" active material. When the energy storage device includes such a lithium transition metal composite oxide, the capacity retention rate can be improved. The molar ratio of the lithium to the total content of the transition metal elements in the first composite oxide is greater than 1. Also, the molar ratio of the manganese to the total content of the transition metal elements is greater than 0.5. By setting the molar ratio of the manganese in the above range, the energy density is improved. More specifically, the first composite oxide is represented by the following formula 1. Li 1+α Me 1-α O2···1 In formula 1, 0<α<1. Me is a transition metal including Mn. Here, the total content (mol) of transition metal elements is X Me , the lithium content (mol) is x Li , manganese content (mol) is x Mn Then, X Li / X Me >1 and X Mn / X Me >0.5.

[0028] In the above formula 1, Me preferably contains Ni or Co in addition to Mn, and more preferably contains Ni and Co. Me may be substantially composed of the three elements Mn, Ni, and Co. However, other transition metal elements may be contained within a range that does not impair the effects of the present invention.

[0029] In the above formula 1, the lower limit of the molar ratio of Ni in the total content of the transition metal elements in the first composite oxide is preferably 0.10, more preferably 0.15. Meanwhile, the upper limit of the molar ratio of Ni is preferably 0.50, more preferably 0.45. By setting the molar ratio of Ni in the above range, the energy density is improved.

[0030] In the above formula 1, the upper limit of the molar ratio of Co in the total content of the transition metal elements in the first composite oxide is preferably 0.23, and more preferably 0.20. On the other hand, the molar ratio of Co may be 0.

[0031] The lithium transition metal composite oxide according to the first composite oxide can be synthesized by various methods such as a solid phase method, a sol-gel method, a hydrothermal method, and a coprecipitation method. Among these, it is preferable to use a composite oxide synthesized by a coprecipitation method, since the transition metal distribution is highly uniform. The coprecipitation method is a method in which a precursor containing a transition metal such as Mn, Ni, or Co is prepared by precipitation (coprecipitation) in an aqueous solution, and a mixture of this precursor and a lithium compound is calcined to synthesize a lithium transition metal composite oxide. As the precursor obtained by the coprecipitation, a hydroxide precursor or a carbonate precursor can be adopted.

[0032] In the first composite oxide, the precursor may be a hydroxide precursor, but by using a carbonate precursor, a precursor and active material with high sphericity can be obtained. Therefore, by using this active material, a positive electrode having a uniform and smooth positive electrode active material layer can be manufactured.

[0033] The first composite oxide preferably has the following differential pore volume: In the pore diameter range of 20 nm to 80 nm in which the differential pore volume, determined by the BJH method from an adsorption isotherm using a nitrogen gas adsorption method, exhibits a maximum value, the lower limit of the peak differential pore volume of the first composite oxide is 0.15 mm 3 / (g nm) is preferred, 0.25 mm 3 / (g nm) is more preferable, 0.50 mm 3 / (g nm) is more preferable, and 0.80 mm 3 On the other hand, the upper limit of the peak differential pore volume of the first composite oxide is preferably 2.8 mm 3 When the nonaqueous electrolyte storage element has a peak differential pore volume in the above range, the contact interface between the first composite oxide and the nonaqueous electrolyte that is highly viscous due to the inclusion of a fluorinated solvent, i.e., the number of reaction sites, can be increased, resulting in further improved discharge capacity and charge / discharge cycle performance.

[0034] The upper limit of the total pore volume of the first composite oxide is 0.09 cm 3 / g is preferred, and 0.08 cm3 By setting the total pore volume to the above upper limit or less, the discharge capacity per volume can be increased.

[0035] The lower limit of the tap density of the first composite oxide is 1.2 g / cm 3 is preferred, and 1.6 g / cm 3 More preferably, 1.7 g / cm 3 By setting the tap density of the lithium transition metal composite oxide to the above lower limit or more, it is possible to improve the discharge capacity per volume, the charge / discharge cycle performance, the high rate discharge performance, etc. On the other hand, the upper limit of this tap density is, for example, 3 g / cm 3 It can be said that:

[0036] The tap density of the lithium transition metal composite oxide is 10 -2 dm 3 Put 2g±0.2g of the powder sample to be measured into a measuring cylinder, and use a tapping device manufactured by REI ELECTRIC CO.LTD. to count 300 times. The volume of the sample to be measured is then divided by the mass of the powder put in to obtain the value.

[0037] The lower limit of the BET specific surface area of ​​the first composite oxide is 3.0 m 2 / g is preferred, 4.0m 2 When the BET specific surface area of ​​the first composite oxide is equal to or greater than the lower limit, the discharge capacity can be improved. 2 / g is preferred, 7m 2 / g is sometimes preferred, and 6m 2 / g may be preferable. When the BET specific surface area of ​​the first composite oxide is within the above range, the contact interface between the first composite oxide and the non-aqueous electrolyte solution, which is highly viscous due to the inclusion of a fluorinated solvent, i.e., the number of reaction sites, can be increased, resulting in a further improvement in discharge capacity. Here, the "BET specific surface area" is determined by immersing the sample in liquid nitrogen and supplying nitrogen gas, which causes nitrogen molecules to physically adsorb to the particle surface, and measuring the pressure and amount of adsorption at that time. A specific measurement method is to measure the amount of nitrogen adsorption (m2 The amount of adsorption thus obtained is divided by the mass (g) of the sample to obtain the BET specific surface area (m 2 / g).

[0038] <Second composite oxide> The second composite oxide contains lithium and transition metal elements including nickel, cobalt, and manganese. The molar ratio of lithium to the total content of the transition metal elements in the second composite oxide is at least 1. By setting the molar ratio of lithium to the total content of the transition metal elements within the above range, the discharge capacity is improved. More specifically, the second composite oxide is represented by the following formula 2. In this case, the lithium transition metal composite oxide is a so-called "LiMeO2 type" active material. Li 1+β (Ni x Co y Mn z )O d 2 In formula 2, 0≦β and x+y+z=1. Theoretically, the value of d is d=2−β. The value of β is preferably 0.1 or less.

[0039] In the above formula 2, the lower limit of the molar ratio of Ni in the total content of the transition metal elements in the second composite oxide is preferably 0.2, more preferably 0.3, and may be 0.4. The upper limit of this molar ratio may be 0.8, more preferably 0.7, and particularly preferably 0.6. By setting the molar ratio of Ni within the above range, a nonaqueous electrolyte storage element having a high discharge capacity per mass and excellent charge / discharge cycle performance can be obtained.

[0040] In the above formula 2, the molar ratio of Co to the total content of the transition metal elements in the second composite oxide is preferably 0.1 to 0.6. By setting the molar ratio of Co to 0.6 or less, an inexpensive nonaqueous electrolyte storage element can be obtained.

[0041] In the formula 2, the lower limit of the molar ratio of Mn in the total content of the transition metal elements in the second composite oxide is preferably 0.1, more preferably 0.2. The upper limit of the molar ratio of Mn is 0.5, more preferably 0.4. By setting the molar ratio of Mn in the above range, the charge-discharge cycle performance is improved.

[0042] In the synthesis of the second composite oxide, by using a hydroxide precursor in a coprecipitation method, it is possible to obtain a dense lithium transition metal composite oxide having an appropriately small specific surface area.

[0043] The second composite oxide preferably has the following differential pore volume: In the pore diameter range of 10 nm to 20 nm in which the differential pore volume, which is determined by the BJH method from an adsorption isotherm using a nitrogen gas adsorption method, has a maximum value, the lower limit of the peak differential pore volume of the second composite oxide is 0.02 mm 3 On the other hand, the upper limit of the peak differential pore volume of the second composite oxide is preferably 0.06 mm 3 When the peak differential pore volume of the second composite oxide is in the above range, the nonaqueous electrolyte storage element can have high charge-discharge cycle performance.

[0044] The upper limit of the total pore volume of the second composite oxide is 0.03 cm 3 / g is preferred, and 0.02 cm 3 By setting the total pore volume to the above upper limit or less, the discharge capacity per volume can be increased.

[0045] The lower limit of the tap density of the second composite oxide is 1.6 g / cm 3 is preferred, and 1.7 g / cm 3 By setting the tap density of the second composite oxide to be equal to or higher than the above lower limit, the discharge capacity per volume of the nonaqueous electrolyte storage element can be increased.

[0046] The lithium transition metal composite oxide preferably contains the first composite oxide, which can improve the discharge capacity and the charge / discharge cycle performance.

[0047] The full width at half maximum of the X-ray diffraction peak in the lithium transition metal composite oxide belongs to the hexagonal space group R3-m, and in the X-ray diffraction diagram using a CuKα tube, the full width at half maximum (FWHM: full width at half maximum) (003) of the diffraction peak at 2θ=18.6°±1° is preferably 0.10° to 0.30° or / and the FWHM (104) of the diffraction peak at 2θ=44.1°±1° is preferably 0.15° to 0.60°. By setting the FWHM of the diffraction peak in the above range, the discharge capacity can be increased. Note that FWHM (104) is an index of the degree of crystallinity from all directions, and the smaller it is, the more advanced the crystallization is. In this specification, "R3-m" is originally written with a bar "-" above the "3" in "R3m."

[0048] The FWHM of the lithium transition metal composite oxide is measured using an X-ray diffractometer (Rigaku, model: MiniFlex II). Specifically, the measurement is performed under the following conditions and procedures. The radiation source is CuKα, the acceleration voltage and current are 30 kV and 15 mA, respectively. The sampling width is 0.01 deg, the scanning time is 14 minutes (scan speed is 5.0), the divergence slit width is 0.625 deg, the receiving slit width is open, and the scattering slit is 8.0 mm. For the obtained X-ray diffraction data, the FWHM(003) of the diffraction peak indexed to the (003) plane in the space group R3-m and present at 2θ=18.6±1° on the X-ray diffraction diagram, and the FWHM(104) of the diffraction peak indexed to the (104) plane and present at 2θ=44±1° on the X-ray diffraction diagram are determined using "PDXL", which is an attached software of the X-ray diffractometer. When analyzing the X-ray diffraction data, the peaks derived from Kα2 are not removed.

[0049] [Measurement target] In the case of a lithium transition metal composite oxide powder before the preparation of a positive electrode (powder before charge / discharge), it is used for the measurement as it is. When taking samples from the positive electrode removed from a disassembled non-aqueous electrolyte secondary battery, before disassembling the battery, discharge the battery at a constant current (0.1C) that is one-tenth of the current value that produces the same amount of electricity as the nominal capacity of the battery when a constant current is applied to the battery for one hour until the battery voltage reaches the lower limit of the specified voltage. Disassemble the battery, remove the positive electrode, and assemble a battery with a metallic lithium electrode as the counter electrode. Test the positive electrode potential at a current value of 10 mA per 1 g of positive electrode mixture until the potential of the positive electrode reaches 2.0 V (vs. Li / Li + ) and adjust to a fully discharged state. Disassemble again and remove the positive electrode. After removing the positive electrode, thoroughly wash the non-aqueous electrolyte attached to the positive electrode using dimethyl carbonate, dry it at room temperature for one day, and then collect the positive electrode mixture on the current collector. In the X-ray diffraction measurement, the sampled positive electrode mixture is used for the measurement. In the measurement of the pore volume, tap density, and specific surface area, the sampled positive electrode mixture is heated in air at 600°C for 4 hours using a small electric furnace to remove the conductive agent and binder, and the positive electrode active material is extracted. The above-mentioned battery disassembly and re-disassembly procedures, as well as the cleaning and drying of the positive plates, are carried out in an argon atmosphere with a dew point of -60°C or less. Here, normal use refers to the case where the storage element is used by adopting the charging and discharging conditions recommended or specified for the storage element, and if a charger is provided for the storage element, the charger is used to use the storage element.

[0050] The positive electrode active material may contain a positive electrode active material other than the first composite oxide or the second composite oxide, for example, a lithium transition metal composite oxide having an α-NaFeO2 type crystal structure other than the first composite oxide or the second composite oxide, a lithium transition metal oxide having a spinel type crystal structure, a polyanion compound, a chalcogen compound, sulfur, etc.

[0051] The content of the positive electrode active material in the positive electrode active material layer is not particularly limited, but the lower limit is preferably 50 mass%, more preferably 80 mass%, and even more preferably 90 mass%, while the upper limit of this content is preferably 99 mass%, and more preferably 98 mass%.

[0052] The conductive agent is not particularly limited as long as it is a material having electrical conductivity. Examples of such conductive agents include carbonaceous materials, metals, conductive ceramics, and the like. Examples of carbonaceous materials include graphitized carbon, non-graphitized carbon, graphene-based carbon, and the like. Examples of non-graphitized carbon include carbon nanofibers, pitch-based carbon fibers, carbon black, and the like. Examples of carbon black include furnace black, acetylene black, ketjen black, and the like. Examples of graphene-based carbon include graphene, carbon nanotubes (CNT), fullerene, and the like. Examples of the shape of the conductive agent include powder and fiber. As the conductive agent, one of these materials may be used alone, or two or more of them may be mixed and used. In addition, these materials may be used in a composite form. For example, a material in which carbon black and CNT are composited may be used. Among these, carbon black is preferable from the viewpoint of electronic conductivity and coatability, and acetylene black is preferable among them.

[0053] The content of the conductive agent in the positive electrode active material layer is preferably 1 mass % or more and 10 mass % or less, and more preferably 3 mass % or more and 9 mass % or less. By setting the content of the conductive agent in the above range, the energy density of the secondary battery can be increased.

[0054] Examples of the binder include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyimide, etc.; elastomers such as ethylene propylene diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, etc.; polysaccharide polymers, etc. The content of the binder in the positive electrode active material layer is preferably 1% by mass or more and 10% by mass or less, more preferably 3% by mass or more and 9% by mass or less.

[0055] Examples of the thickener include polysaccharide polymers such as carboxymethyl cellulose (CMC), methyl cellulose, etc. In addition, when the thickener has a functional group that reacts with lithium, it is preferable to deactivate this functional group in advance by methylation or the like.

[0056] The filler is not particularly limited. Examples of the filler include polyolefins such as polypropylene and polyethylene, inorganic oxides such as silicon dioxide, alumina, titanium dioxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicates, hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide, carbonates such as calcium carbonate, poorly soluble ion crystals such as calcium fluoride, barium fluoride, and barium sulfate, nitrides such as aluminum nitride and silicon nitride, and mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, or artificial products thereof.

[0057] The intermediate layer is a coating layer on the surface of the positive electrode substrate, and contains a conductive agent such as a carbonaceous material to reduce the contact resistance between the positive electrode substrate and the positive electrode active material layer. As with the negative electrode, the configuration of the intermediate layer is not particularly limited, and can be formed, for example, from a composition containing a resin binder and conductive particles.

[0058] [Nonaqueous electrolyte] The non-aqueous electrolyte contains a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent.

[0059] (Non-aqueous solvent) The non-aqueous solvent includes a fluorinated solvent, such as a fluorinated carbonate, a fluorinated ester, or a fluorinated ether.

[0060] The fluorinated carbonate may be a fluorinated cyclic carbonate or a fluorinated chain carbonate.The fluorinated cyclic carbonate may be fluorinated ethylene carbonate such as fluoroethylene carbonate (FEC), difluoroethylene carbonate, fluoromethylethylene carbonate, trifluoroethylethylene carbonate, fluorinated propylene carbonate, fluorinated butylene carbonate, etc.The fluorinated chain carbonate may be trifluoroethylmethyl carbonate (TFEMC), bis(trifluoroethyl)carbonate (FDEC), etc.

[0061] Examples of fluorinated esters include methyl 3,3,3-trifluoropropionate (FMP), 2,2,2-trifluoroethyl acetate (FEA), methyl difluoroacetate (MFA), ethyl difluoroacetate (EFA), tris(2,2,2-trifluoroethyl)phosphate (TFEP), and tris(2,2,2-trifluoroethyl)borate (TFEB).

[0062] Examples of fluorinated ethers include 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether and 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether (TFEE).

[0063] From the viewpoint of improving the charge-discharge cycle performance, the fluorinated solvent is preferably a fluorinated cyclic carbonate or a fluorinated chain carbonate, more preferably a fluorinated ethylene carbonate, and even more preferably a fluoroethylene carbonate. The fluoroethylene carbonate has high oxidation resistance and is highly effective in suppressing side reactions (such as oxidative decomposition of the nonaqueous solvent) that may occur during charging and discharging of the nonaqueous electrolyte storage element.

[0064] The above fluorinated solvents can be used alone or in combination of two or more.

[0065] The non-aqueous solvent may contain an organic solvent other than the fluorinated solvent. Examples of the other organic solvent include cyclic carbonates other than the fluorinated solvent, chain carbonates, esters, ethers, amides, sulfones, lactones, nitriles, etc. Among these, it is preferable to use at least a carbonate, and it is more preferable to use a cyclic carbonate and a chain carbonate in combination. The carbonate may be a carbonate that does not have a substituent, or may be a carbonate that has a substituent. Examples of the substituent include a hydroxyl group, a halogen atom, etc.

[0066] Examples of cyclic carbonates other than the above-mentioned fluorinated cyclic carbonates include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylene carbonate (VC), vinylethylene carbonate (VEC), chloroethylene carbonate, styrene carbonate, catechol carbonate, 1-phenylvinylene carbonate, 1,2-diphenylvinylene carbonate, etc. Examples of chain carbonates other than the above-mentioned fluorinated chain carbonates include diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diphenyl carbonate, etc. Examples of the above-mentioned esters include 3,3,3-methyl trifluoropropionate (FMP), etc. Examples of the above-mentioned sulfones include sulfolane (SL), ethyl isopropyl sulfone (EiPSO2), ethyl methyl sulfone (EMSO2), etc. Examples of the sulfite include diethyl sulfite (DES) and dimethyl sulfite (DMS).

[0067] The lower limit of the total content of the fluorinated solvent in the nonaqueous solvent is preferably 10% by volume, more preferably 20% by volume, and even more preferably 25% by volume. On the other hand, the upper limit of the total content of the fluorinated solvent may be 100%. By setting the total content of the fluorinated solvent in the above range, the charge-discharge cycle performance can be improved.

[0068] (Electrolyte salt) The electrolyte salt may be any known electrolyte salt that is commonly used as an electrolyte salt for a general non-aqueous electrolyte storage element, including lithium salt, sodium salt, potassium salt, magnesium salt, onium salt, etc., with lithium salt being preferred.

[0069] Examples of the lithium salt include inorganic lithium salts such as LiPF6, LiPO2F2, LiBF4, LiClO4, and LiN(SO2F)2, and lithium salts having a fluorohydrocarbon group such as LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, and LiC(SO2C2F5)3. Among these, inorganic lithium salts are preferred, and LiPF6 is more preferred.

[0070] The lower limit of the content of the electrolyte salt in the nonaqueous electrolyte solution is 0.1 mol dm - 3 is preferred, and 0.3 mol dm -3 is more preferred, and 0.5 mol dm -3 On the other hand, the upper limit is not particularly limited, but is preferably 3 mol dm -3 is preferred, and 2 mol dm -3 is more preferred.

[0071] (Additives, etc.) The non-aqueous electrolyte may contain other additives other than the electrolyte salt, as long as they do not impair the effects of the present invention. Examples of the other additives include various additives contained in general non-aqueous electrolyte storage elements. The total content of the additives in the non-aqueous electrolyte is preferably 10% by mass or less, and more preferably 5% by mass or less.

[0072] The non-aqueous electrolyte solution can usually be obtained by adding and dissolving components such as the electrolyte salt in the non-aqueous solvent.

[0073] [Separator] As the separator, for example, a woven fabric, a nonwoven fabric, a porous resin film, etc. are used. Among these, a porous resin film is preferable from the viewpoint of strength, and a nonwoven fabric is preferable from the viewpoint of the liquid retention of a nonaqueous electrolyte. As the main component of the separator, a polyolefin such as polyethylene or polypropylene is preferable from the viewpoint of strength, and a polyimide or aramid is preferable from the viewpoint of oxidation decomposition resistance. These resins may also be combined.

[0074] An inorganic layer may be disposed between the separator and the electrode. This inorganic layer is a porous layer also called a heat-resistant layer. A separator having an inorganic layer formed on one side of a porous resin film may also be used. The inorganic layer is usually composed of inorganic particles and a binder, and may contain other components. The inorganic layer may be disposed on the surface facing the positive electrode, may be disposed on the surface facing the negative electrode, or may be disposed on both sides. In general, the inorganic layer is disposed on the surface facing the positive electrode in order to suppress denaturation caused by the action of the positive electrode. On the other hand, in the nonaqueous electrolyte storage element of the present invention in which the negative electrode active material contains lithium metal, the inorganic layer is preferably disposed on the surface facing the negative electrode in order to reduce the risk of short circuit caused by the deposition of metallic lithium. Therefore, the inorganic layer is preferably disposed on both sides.

[0075] [Specific configuration of non-aqueous electrolyte storage element] The shape of the nonaqueous electrolyte storage element of this embodiment is not particularly limited, and examples thereof include a cylindrical battery, a prismatic battery, a flat battery, a coin battery, and a button battery.

[0076] FIG 1 shows a nonaqueous electrolyte storage element 1 as an example of a prismatic battery. The figure is a see-through view of the inside of a case 3. An electrode body 2 having a positive electrode and a negative electrode wound with a separator sandwiched therebetween is housed in the prismatic case 3. The positive electrode is electrically connected to a positive electrode terminal 4 via a positive electrode lead 41. The negative electrode is electrically connected to a negative electrode terminal 5 via a negative electrode lead 51. A nonaqueous electrolyte is injected into the case 3.

[0077] [Method of manufacturing non-aqueous electrolyte storage element] The method for producing the nonaqueous electrolyte storage element according to the present embodiment can be appropriately selected from known methods. The method for producing the nonaqueous electrolyte storage element according to the present embodiment includes, for example, a step of preparing an electrode body, a step of preparing a nonaqueous electrolyte, and a step of housing the electrode body and the nonaqueous electrolyte in a case. The step of preparing the electrode body includes a step of preparing a positive electrode and a negative electrode, and a step of forming the electrode body by stacking or winding the positive electrode and the negative electrode with a separator interposed therebetween.

[0078] The process of housing the non-aqueous electrolyte in the case can be appropriately selected from known methods. For example, when using a liquid non-aqueous electrolyte, the non-aqueous electrolyte is injected from an injection port formed in the case, and then the injection port is sealed. Details of the other elements constituting the storage element obtained by this manufacturing method are as described above.

[0079] [Other embodiments] The nonaqueous electrolyte storage element according to the present invention is not limited to the above-mentioned embodiment, and various modifications may be made without departing from the scope of the present invention. For example, the configuration of one embodiment may be added to the configuration of another embodiment, and part of the configuration of one embodiment may be replaced with the configuration of another embodiment or a well-known technique. Furthermore, part of the configuration of one embodiment may be deleted. Also, a well-known technique may be added to the configuration of one embodiment.

[0080] In the above embodiment, the nonaqueous electrolyte storage element is mainly a nonaqueous electrolyte secondary battery, but other nonaqueous electrolyte storage elements may be used. Examples of other nonaqueous electrolyte storage elements include capacitors (electric double layer capacitors, lithium ion capacitors), etc. Examples of nonaqueous electrolyte secondary batteries include lithium ion nonaqueous electrolyte secondary batteries.

[0081] The present invention can also be realized as an electricity storage device including a plurality of the nonaqueous electrolyte storage elements. In addition, a single or a plurality of the nonaqueous electrolyte storage elements (cells) of the present invention can be used to form an electricity storage unit, and this electricity storage unit can be used to form an electricity storage device. The electricity storage device can be used as a power source for automobiles such as electric vehicles (EVs), hybrid vehicles (HEVs), and plug-in hybrid vehicles (PHEVs). Furthermore, the electricity storage device can be used in various power sources such as engine starting power sources, auxiliary power sources, and uninterruptible power sources (UPSs).

[0082] An electric storage device according to an embodiment of the present invention includes two or more nonaqueous electrolyte storage elements and includes one or more nonaqueous electrolyte storage elements according to the above embodiment (hereinafter, referred to as "second embodiment"). It is sufficient that the technology according to one embodiment of the present invention is applied to at least one nonaqueous electrolyte storage element included in the electric storage device according to the second embodiment, and the electric storage device may include one nonaqueous electrolyte storage element according to the above embodiment and one or more nonaqueous electrolyte storage elements not related to the above embodiment, or may include two or more nonaqueous electrolyte storage elements according to the above embodiment. FIG. 2 shows an example of an electric storage device 30 according to the second embodiment, which is further assembled into an electric storage unit 20, each of which is an assembly of two or more electrically connected nonaqueous electrolyte storage elements 1. The electric storage device 30 may include a bus bar (not shown) that electrically connects two or more nonaqueous electrolyte storage elements 1, and a bus bar (not shown) that electrically connects two or more electric storage units 20. The electric storage unit 20 or the electric storage device 30 may include a state monitor (not shown) that monitors the state of one or more nonaqueous electrolyte storage elements.

[0083] (Measurement of total pore volume and peak differential pore volume) The total pore volume and peak differential pore volume of the positive electrode active material are measured by the following method. 1.00 g of the powder of the measurement sample is placed in a measurement sample tube and dried under reduced pressure at 120°C for 6 hours and then at 180°C for 6 hours to thoroughly remove moisture in the measurement sample. Next, by a nitrogen gas adsorption method using liquid nitrogen, isotherms on the adsorption side and desorption side are measured within a relative pressure P / P0 (P0 = approximately 770 mmHg) range of 0 to 1. Then, a cumulative pore volume curve is obtained by calculation using the desorption side isotherm by the BJH method. From this curve, the total pore volume (cm 3 Next, the cumulative pore volume curve is linearly differentiated to obtain the value of pore diameter (nm) on the horizontal axis and differential pore volume (mm 3 A differential pore volume curve is obtained in which the differential pore volume curve is expressed as / (g·nm). In this specification, the "peak differential pore volume" refers to the value on the vertical axis corresponding to the point where the differential pore volume curve shows the maximum value. A large "peak differential pore volume" means that there are many pores with a certain pore diameter. In this specification, the "pore diameter at which the differential pore volume shows the maximum value" refers to the value on the horizontal axis corresponding to the point where the differential pore volume curve shows the maximum value. EXAMPLES

[0084] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0085] [Example 1] (Preparation of non-aqueous electrolyte) Fluoroethylene carbonate (FEC) and trifluoroethyl methyl carbonate (TFEMC) were mixed in a volume ratio of FEC:TFEMC = 30:70, and 1 mol dm LiPF6 was added to the mixed solvent. -3 This was dissolved in water at a concentration of 100% by weight to prepare a non-aqueous electrolyte solution.

[0086] (Preparation of positive electrode) The positive electrode active material used was a first composite oxide, which was a lithium transition metal composite oxide having an α-NaFeO2 type crystal structure shown in Table 1. Here, the molar ratio of Li to the total content of the transition metal elements in the first composite oxide was 1.33, and the transition metal elements in the second composite oxide consisted of Ni and Mn, and were contained in a molar ratio of Ni:Mn=34:66.

[0087] A positive electrode paste was prepared using N-methylpyrrolidone (NMP) as a dispersion solvent, containing the positive electrode active material, acetylene black (AB) as a conductive agent, and polyvinylidene fluoride (PVdF) as a binder in a mass ratio of 94:4.5:1.5. The positive electrode paste was applied to one side of a 15 μm thick aluminum foil as a positive electrode substrate, dried, pressed, and cut to prepare a positive electrode having a positive electrode active material layer arranged in a rectangular shape of 30 mm wide and 40 mm long. The positive electrode plate had a thickness of approximately 70 μm, and the positive electrode mixture was 12 mg / cm per unit area. 2 The positive electrode was dried under reduced pressure at 100° C. for 14 hours or more before use.

[0088] (Preparation of negative electrode) A lithium metal plate with a width of 31 mm, a length of 42 mm, and a thickness of 600 μm was used as the negative electrode plate. The lithium metal plate was pressed at a pressure of 1.4 MPa through a metal-resin composite film, and had a metallic luster. In addition, a stainless steel negative electrode substrate was connected to only the end of the lithium metal plate with a length of 5 mm.

[0089] (Preparation of non-aqueous electrolyte storage element) A polypropylene microporous membrane having a thickness of 27 μm was used as the separator. Three of the separators were stacked and the periphery was fused except for one side to produce a pouch-shaped separator having two pouches. The negative electrode was inserted into one of the pouches of the pouch-shaped separator, and the positive electrode was inserted into the other pouch so that the surface on which the positive electrode active material layer was arranged faced the negative electrode. In this way, a nonaqueous electrolyte storage element was produced.

[0090] The electrode group was housed in a metal resin composite film case so that the open ends of the lead terminals previously connected to the positive and negative electrodes, respectively, were exposed to the outside, and the case was sealed except for a portion that would become a liquid injection hole. After the nonaqueous electrolyte was injected, the liquid injection hole was hermetically sealed. In this manner, a nonaqueous electrolyte storage element was produced.

[0091] [Examples 2 to 6 and Comparative Examples 1 to 3] Non-aqueous electrolyte storage elements of Examples 2 to 6 and Comparative Examples 1 to 3 were obtained in the same manner as in Example 1, except that the positive electrode active material and solvent were as shown in Table 1. In the following tables, "-" indicates that the corresponding component was not contained.

[0092] [Reference example 1] Graphite was used as the negative electrode active material. A negative electrode paste was prepared by mixing graphite, styrene butadiene rubber, and carboxymethyl cellulose in a mass ratio of 96.7:2.1:1.2 (solid content equivalent) and using water as a dispersion solvent. The negative electrode paste was dispersed in a 10 mg / cm2 negative electrode mixture per unit area. 2 The negative electrode active material layer was formed by pressing the negative electrode active material layer with a roller press, and then dried under reduced pressure at 100° C. for 14 hours to remove moisture from the negative electrode. The negative electrode thus obtained was used, and the nonaqueous electrolyte storage element of Reference Example 1 was obtained in the same manner as in Example 1, except that the type and amount of the solvent in the nonaqueous electrolyte used were as shown in Table 1.

[0093] (Initial charge / discharge) For each of the obtained nonaqueous electrolyte storage elements, two cycles of initial charge and discharge were performed under the following conditions in a 25°C environment. Charging was performed by constant current constant voltage (CCCV) charging with a charging current of 0.1C and a charging voltage of 4.7V, and the charging termination condition was until the charging current reached 0.05C. Discharging was performed by constant current (CC) discharging with a discharging current of 0.1C and a discharge termination voltage of 2.0V. A rest period of 10 minutes was provided after each charging and discharging. The discharge capacity in the second cycle was taken as the "initial discharge capacity [mAh / g]".

[0094] (Charge-discharge cycle test) Next, for each nonaqueous electrolyte storage element after the initial charge and discharge, a charge and discharge cycle test was carried out for 25 cycles in an environment of 25° C. under the following conditions. Charging was performed at constant current, constant voltage (CCCV) with a charging current of 0.33 C and an end-of-charge voltage of 4.7 V, and the charge termination condition was that the charging current reached 0.05 C. Discharging was performed at a constant current of 0.33 C and an end-of-charge voltage of 2.0 V. A rest period of 10 minutes was provided after each charging and discharging.

[0095] However, for the nonaqueous electrolyte storage element of Reference Example 1 using graphite as the negative electrode active material, the cut-off voltage for the initial charge / discharge and charge / discharge cycle tests was 4.6V.

[0096] (Discharge capacity confirmation test after 25 cycles) Next, one cycle of charging and discharging was performed under the same charging and discharging conditions as the above initial charging and discharging, and the discharge capacity at this time was defined as "discharge capacity after 25 cycles (mAh / g)." The percentage of the discharge capacity after 25 cycles of the test relative to the initial discharge capacity was defined as the "capacity retention rate after charge / discharge cycles (%)."

[0097] Table 1 shows the peak differential pore volume, the pore diameter at which the differential pore volume is maximum, the total pore volume, the initial discharge capacity, and the capacity retention rate after charge-discharge cycling.

[0098] [Table 1]

[0099] As shown in Table 1 above, it was confirmed that the nonaqueous electrolyte storage elements according to Examples 1 to 6, in which the nonaqueous electrolyte contains a fluorinated solvent and the positive electrode active material contains the first composite oxide or the second composite oxide, which is a lithium transition metal composite oxide having an α-NaFeO2 structure, have both high discharge capacity and capacity retention rate after charge / discharge cycles. Among these, Examples 1 to 3, in which the positive electrode active material is the first composite oxide, had excellent capacity retention rate after charge / discharge cycles. In particular, when the pore diameter at which the differential pore volume is maximized is in the range of 20 nm or more and 80 nm or less, the peak differential pore volume of the first composite oxide is 0.8 mm 3 / (g·nm) or more, more excellent effects were obtained in terms of both the discharge capacity and the capacity retention rate after charge / discharge cycling.

[0100] In contrast, in Comparative Examples 1 to 3 in which the non-aqueous electrolyte did not contain a fluorinated solvent, the capacity retention rate after charge-discharge cycles was poor, even though the positive electrode active material was the first composite oxide or the second composite oxide.

[0101] On the other hand, in the reference example in which graphite was used as the negative electrode active material, the capacity retention rate after charge-discharge cycles was good even though the non-aqueous electrolyte did not contain a fluorinated solvent. From this, it is considered that the effect of improving the capacity retention rate after charge-discharge cycles by the combination of the positive electrode active material containing the first composite oxide or the second composite oxide and the fluorinated solvent is a unique effect on the negative electrode containing lithium metal as the negative electrode active material.

[0102] The above results demonstrate that the nonaqueous electrolyte storage element equipped with a negative electrode having a negative electrode active material layer containing lithium metal has excellent discharge capacity and charge / discharge cycle performance. [Industrial Applicability]

[0103] The present invention can be applied to nonaqueous electrolyte electricity storage elements and electricity storage devices used as power sources for electronic devices such as personal computers and communication terminals, and automobiles. [Explanation of symbols]

[0104] 1. Nonaqueous electrolyte storage element 2 Electrode body 3 Cases 4 Positive terminal 41 Positive lead 5 Negative terminal 51 Negative lead 20 Energy Storage Unit 30 Energy storage device

Claims

1. a negative electrode having a negative electrode active material layer containing a negative electrode active material; a positive electrode having a positive electrode active material layer containing a positive electrode active material; Non-aqueous electrolyte Equipped with the non-aqueous electrolyte contains a fluorinated solvent, the negative electrode active material contains lithium metal, The positive electrode active material is α-NaFeO 2 The lithium transition metal composite oxide has a structure, the lithium transition metal composite oxide is a first composite oxide, the first composite oxide contains a transition metal element including manganese and lithium, a molar ratio of the lithium to the total content of the transition metal elements in the first composite oxide is greater than 1, and a molar ratio of the manganese to the total content of the transition metal elements is greater than 0.5, A nonaqueous electrolyte storage element in which the peak differential pore volume of the first composite oxide is 0.50 mm3 / (g·nm) or more in a pore diameter range of 40 nm or more and 80 nm or less in which the differential pore volume, as determined by the BJH method from an adsorption isotherm using a nitrogen gas adsorption method, shows a maximum value.

2. A negative electrode having a negative electrode active material layer containing a negative electrode active material; a positive electrode having a positive electrode active material layer containing a positive electrode active material; Non-aqueous electrolyte Equipped with the non-aqueous electrolyte contains a fluorinated solvent, the negative electrode active material contains lithium metal, the positive electrode active material contains a lithium transition metal composite oxide having an α-NaFeO 2 structure; the lithium transition metal composite oxide is a second composite oxide, the second composite oxide contains transition metal elements including nickel, cobalt, and manganese, and lithium, a molar ratio of the lithium to a total content of the transition metal elements in the second composite oxide is 1 or more, and a molar ratio of the manganese to a total content of the transition metal elements in the second composite oxide is 0.5 or less, A nonaqueous electrolyte storage element in which the peak differential pore volume of the second composite oxide is 0.06 mm3 / (g·nm) or less when the pore diameter at which the differential pore volume has a maximum value determined by the BJH method from an adsorption isotherm using a nitrogen gas adsorption method is in the range of 10 nm to 20 nm.

3. 3. An electricity storage device comprising two or more nonaqueous electrolyte storage elements, the nonaqueous electrolyte storage element being at least one of the nonaqueous electrolyte storage elements according to claim 1 or 2.

Citation Information

Patent Citations

  • Nonaqueous electrolyte secondary battery

    JP2011034943A

  • Active material for nonaqueous electrolyte battery, and nonaqueous electrolyte battery

    JP2011124154A

  • Active material for non-aqueous electrolyte secondary cell, method for manufacturing active material for non-aqueous electrolyte secondary cell, electrode for non-aqueous electrolyte secondary cell, and non-aqueous electrolyte secondary cell

    WO2013084923A1

  • Positive electrode active material for non-aqueous electrolyte secondary batteries and method for producing same, electrode for non-aqueous electrolyte secondary batteries, and non-aqueous electrolyte secondary battery

    WO2016190419A1

  • Nonaqueous electrolyte and nonaqueous electrolyte electricity storage element

    WO2019031598A1